How product market reforms lubricate shock adjustment in the euro area - Pelkmans, Jacques; Montoya, Lourdes Acedo; Maravalle, Alessandro; European Commission : Directorate-General for Economic and Financial Affairs (Brussels : Office for Infrastructure and Logistics in Brussels, 2008)
The essay sets out what product market reforms are, as well as the main measurement issues, followed by an analysis of how such reforms lubricate adjustment processes in EMU, in particular via the "competitiveness channel". Attention is paid to the short-run and longer-run aspects of adjustments to shocks and the scant empirical evidence on the role of product markets in adjustment is discussed. The essay investigates empirically the need for product market reforms in the euro area, based on the KLEMS data set. Two questions are addressed: how likely is it for euro area countries to experience an asymmetric shock, and what empirical evidence can we deduce about eurozone countries' capacities to adjust to asymmetric shocks? The approach is disaggregated and highlights (especially services) sectors with relatively greater adjustment problems. The record of product market reforms of the euro area countries is briefly summarized. The paper shows that substantial reforms have been undertaken, yet, there is considerable evidence that the eurozone, and in particular with respect to services, could significantly intensify product market reforms and thereby augment the net benefits of having a single currency. Subsequently, product market reforms are placed in the context of wider reforms efforts (complementarities e.g. with labour and financial markets) as well as in the two-tier institutional structure of the euro area and the EU at large (given cross-border spillovers and the case for coordination). Designing reforms in this euro area context is briefly discussed. A final section with five "policy messages" concludes the essay.
Economic Papers.